posted by .

P=(2J+1)exp(-(BJ(J+1))/kT) where B, k and T are constants

a. Show that dP/dJ=(2-(B(2J+1)^2)/kT)exp(-BJ(J+1)/kT)

b. Show that P exhibits a maximum and determine the expression for Jmax

c. Find the value of P when J=0 and the limiting value of P when J becomes large(infinity).

  • Maths -

    I would skip a) and do b) by differentiating Log(P). For positive P, Log(P) has a maximum at a point if and only if P is maximal there.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Physics/Math

    A can of sardines is made to move along an x axis from x1 = 0.2 m to x2 = 1.2 m by a force given by F = iF0exp(-0.4x), with x in meters and F0 = 4.5 N. (Here exp is the exponential function.) How much work is done on the can by the …
  2. (expi)^i

    This question is not well defined. By 'expi' do you mean exp(i)?
  3. Calculus II

    What is sin(i) -- (sin of the imaginary number, i) What is cos(i)-- cosine of the imaginary number, i orrr tan(1+i) You can derive these things from the equation: Exp(i x) = cos(x) + i sin(x) ---> sin(x) = [Exp(ix) - Exp(-ix)]/(2i) …
  4. maths-complex numbers

    by using the substitution w = z^3, find all the solutions to z^6 - 8z^3 +25 = 0 in complex numbers, and describe them in polar form, using @(theta) to denote the angle satisfying tan@ = 3/4 ( note simply leave @ as it is, don't calculate …
  5. Math/Calculus

    How would I evaluate the following integral by using integration by parts?
  6. calc: arc length

    find the exact length of this curve: y = ( x^3/6 ) + ( 1/2x ) 1/2 <or= x <or= 1 im looking over my notes, but i'm getting stuck. here's my work so far: A ( 1 , 2/3 ) B ( 1/2 , 49/48 ) y' = [1/6 (3x^2)] + [1/2 (-1x^-2)] y' = ( …
  7. Maths

    Rearrange for T and J; n=(2J+1)exp(-(BJ(J+1))/(KT)) where B and K are constants
  8. Maths

    Transform the following relationships/funtions into linear form and identify expressions for the x and y variables. a) (x^2/a^2) + (y^2/b^2) = 1 where a and b are constants. b) k(T) = (kT/h)exp((deltaS)/R)exp(-(deltaH)/RT) where k, …
  9. maths

    help find the general solution of the following first order differential equation. t*(dy/dt) = (-y/t) + ((exp(1/t)/t^3) could you show steps in working to sol.
  10. maths

    find the general solution of the following first order differential equation. dx/dt = t*x + 6*t(exp)-t^2 pls show working

More Similar Questions